EXPLORING THE HARMONIZATION OF RPJMDES AND APBDES: A STUDY ROWOTAMTU VILLAGE CASE - Aprelita, Reny; Paramitha , Diana; Reyvalda , Noradina; Khodijah, Aza Citra; Syakirin, Robbihyina; Ishaq, Indra Maulana; Yudhistira, Prillinaya; Ardhiarisca, Oryza (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Harmonization between the Village Medium-Term Development Plan (RPJMDes) and the Village Revenue and Expenditure Budget (APBDes) is crucial for effective, transparent, and sustainable village development. However, in various villages across Indonesia, including Rowotamtu Village, Rambipuji Distrik, challenges remain in maintaining alignment between medium-term planning and annual budgeting. This study aims to analyze the extent to which the Village Budget (APBDes) allocation aligns with the development priorities outlined in the RPJMDes and identify factors that hinder and support this alignment. This study employed a qualitative descriptive method, conducted through interviews with the Finance and Planning Heads, and analyzed the RPJMDes and APBDes documents. The results indicate that most priority programs are included in the APBDes, but budget revisions occur frequently annually due to regulatory changes, changes in funding levels, urgent needs, and limited village human resources. This mismatch leads to program delays, reduced activities, and decreased public trust, particularly in social programs such as the Direct Cash Assistance (BLT). The study concluded that strengthening the capacity of village officials, continuous coordination between government institutions, and optimizing the use of the village financial system are important strategies to improve the alignment between the RPJMDes and the APBDes in a sustainable manner. Keywords: RPJMDes; APBDes; Planning-Budgeting Harmonization; Village Government; Stewardship; Rowotamtu Village.